Cancer-associated proteins in effusion fluids. Issue 6 (June 1977) - Booth, S N; Lakin, G; Dykes, P W; Burnett, D; Bradwell, A R
Abstract : Two cancer-associated proteins, carcinoembryonic antigen (CEA) and pregnancy-associated alpha2 glycoprotein (PAG), together with 13 normal serum proteins were measured in the serum and effusion fluid of patients with ascites and pleural effusions. The results indicate that CEA measurement in effusion fluid is more effective than serum measurement in distinguishing cancerous from congestive or inflammatory effusions. Comparisons with the results of cytological examination suggest that fluid CEA estimation may prove a useful clinical tool. Serum PAG levels were higher in patients with cancer, but fluid determination offers no advantage in separating the disease groups. Similarly, the estimation of individual normal serum proteins in effusion fluids is unlikely to be of diagnostic value.